HYGIENE FROM THE HEART: THE RISE OF SHARIA COMPLIANT HOTEL IN INDONESIA AFTER COVID-19 PANDEMIC - Maulana, Noveri; Oktaviaman, Restia; Farah, Yasmine (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2020)
The development of Sharia-compliant hotel (SCH) in Indonesia is rapidly growing since 2012. However, the COVID-19 pandemic has changed the business development of SCH and in the Halal Tourism Industry. This paper aims to develop an alternative strategy for SCH to rebuild the market after the pandemic situation. This research is specified the marketing strategy to attract domestic tourist, especially Muslim tourist to prefer Sharia-compliant hotel in their travelling destinations. As the primary object of the research, this paper is using a well-known sharia hotel in Jakarta as the single case study analysis. Mix method approach is implemented in this study, which used quantitative and qualitative data. All the data are formulated in Threat, Opportunity, Weakness, Strength (TOWS) Matrix. The result of strategy formulation in the matrix will produce several alternatives of marketing strategy, which might be implemented by the SCH management in Indonesia. Survey was conducted before the COVID-19 pandemic to 197 respondents to evaluate the service quality and the decision-making process of the consumer towards SCH in Jakarta. In-depth interview and focus group discussion (FGD) were conducted with the board of directors to follow up the survey and to implement internal validity with the hotel management. Documents review and observation were also implemented. Based on strategy formulation in TOWS Matrix, this research is proposed three strategic marketing programs which could be implemented by Sharia Compliance Hotel toward the new adaptation era after the pandemic. Those strategies are discussed in the result analysis.